The Impact of Drug and Alcohol Consumption and Socio-demographic Variables on the Age of First Selling Sex among Iranian Female Sex Workers - Mahboobeh Mousavi-Ramezanzade; Yunes Jahani; Moghaddameh Mirzaee; Hamid Sharifi (Addiction and Health, 2020)
Background: A significant proportion of Female Sex Workers (FSWs) as a vulnerable population begin sellingsex at an early age, which may lead the person to develop sexually-transmitted infections (STIs) and humanimmunodeficiency virus (HIV). Thus, this study seeks to identify the factors which influence the age of firstsex for sale among the Iranian FSWs.Methods: In 2010, 872 FSWs from 21 centers in 12 Iranian provinces were selected through multistagesampling and were interviewed individually by a standard questionnaire. Survival analysis of intervalcensored data was used to investigate factors which influence the age of first selling sex. The collected datawere analyzed using Weibull parametric model and the hazard ratio (HR) index was reported. The softwareemployed in this study was R version 3.4.2 and icenReg package was used.Findings: The mean age of first selling sex was 24.94 ± 7.34 years. About 22% of the participants started tosell sex before the age of 18. The risk of experiencing the first selling sex was 23% higher in those individualswho had experienced alcohol consumption (HR = 1.23) and 51% higher in those who had drug injections(HR = 1.51). Also, age, education, and marital status were significant variables.Conclusion: In order to cope with the issue of first selling sex at an early age, the following strategies aresuggested: providing necessary trainings and building culture about the dangers of alcohol consumption anddrug injections, poverty reduction, facilitating education and marriage for young females, and combating sextrafficking